2008
DOI: 10.1016/j.juro.2007.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Radical Nephrectomy for pT1a Renal Masses May be Associated With Decreased Overall Survival Compared With Partial Nephrectomy

Abstract: Our results suggest that, compared with partial nephrectomy, radical nephrectomy is associated with decreased overall survival in younger patients with small renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
330
3
21

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(375 citation statements)
references
References 21 publications
11
330
3
21
Order By: Relevance
“…Thompson et al first reported that radical nephrectomy was associated with decreased survival in patients who had a single renal cortical tumor 4 cm compared with partial nephrectomy, suggesting that this effect might be related to a loss of renal function that outweighed any oncologic benefit. 16 Pettus et al subsequently reported that moderate and severe renal dysfunction before surgery were associated with decreased overall survival in patients undergoing partial or radical nephrectomy. 17 Hollingsworth et al, in a population-based competing risk analysis, demonstrated that the competing-cause mortality for elderly patients (aged 70 years) was 28% and concluded that active surveillance might be a reasonable strategy for some tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson et al first reported that radical nephrectomy was associated with decreased survival in patients who had a single renal cortical tumor 4 cm compared with partial nephrectomy, suggesting that this effect might be related to a loss of renal function that outweighed any oncologic benefit. 16 Pettus et al subsequently reported that moderate and severe renal dysfunction before surgery were associated with decreased overall survival in patients undergoing partial or radical nephrectomy. 17 Hollingsworth et al, in a population-based competing risk analysis, demonstrated that the competing-cause mortality for elderly patients (aged 70 years) was 28% and concluded that active surveillance might be a reasonable strategy for some tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that both open and laparoscopic partial nephrectomy produce superior functional outcomes and oncologic outcomes that are at least equivalent to the outcomes produced after radical nephrectomy for selected tumors. 16,[19][20][21][22] Percutaneous tumor ablation and active surveillance are considered for patients who may be poor surgical candidates. Although it is not quite as effective as partial nephrectomy, approximately 80% of patients are disease-free after thermal ablation, and this remains a valid nephron-sparing intervention for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of nephron-sparing surgery focuses not only on avoiding chronic renal insufficiency, but also to decrease the incidence of cardiovascular events and death. 8,9,10 Therefore, in patients with a renal mass ≤ 4cm (cT1a), partial nephrectomy is the new gold standard. It has even been suggested that tumors <7cm (cT1b) should be managed with parital nephrectomy when surgically feasible.…”
Section: Review Of Management Options For the Ct1 Renal Massmentioning
confidence: 99%
“…The majority of the urologic literature has demonstrated that most small RCNs have a slow growth rate (GR) and low risk of metastasis. 10 A summary of the contemporary AS series (820 tumors) show a growth rate of 0.27cm/year with 21% undergoing delayed intervention (Table 1). Only 12 (1.6%) lesions progressed to metastatic disease with only 1 cancer specific death.…”
Section: Review Of Management Options For the Ct1 Renal Massmentioning
confidence: 99%
“…Bununla birlikte KBH olan hastalarda kardiyovasküler mortalite, KBH olmayanlara göre daha fazladır (32/1.000'e karşı 16/1.000) (8). Genç (<65 yaş) ve küçük renal kitleli (<4 cm) hastalarda RN ile NKC karşılaştırıldığında, RN'nin daha kısa genel sağkalım ile ilişkili olduğu gösterilmiştir (9). Görüntüleme ve ameliyat tekniklerindeki bu gelişmeler sonucunda günümüzde RHK hastalarında onkolojik başarı artık tek başına başarı olarak kabul edilemez.…”
Section: Introductionunclassified